Adsorption characteristics of alumina nanoparticles for the removal of hazardous dye, Orange G from aqueous solutions - Banerjee, S.; Dubey, S.; Gautam, R.K.; Chattopadhyaya, M.C.; Sharma, Y.C. (Elsevier B.V., 2019)
The application of nanomaterials for water treatment has gained impetus in recent years. Nano-adsorbents offer significant decontamination potential due to their unique characteristics. Present study deals with synthesis and application of alumina nanoparticles for removal of an anionic dye, Orange G (OG) from aqueous solutions. The properties of synthesized nanoparticles were investigated by FTIR, TG/DTA, XRD, TEM, SEM, EDX and N2 adsorption-desorption techniques. The effect of various important parameters on dye removal was examined and adsorption was found to be highly pH dependent and maximum removal of 98.4% was observed at pH 2.5. The presence of interfering anions such as SO4 2−, PO4 3−, and C2O4 2− was found to be limiting factor of the adsorption process. The kinetic results demonstrated that the sorption process was described by pseudo-second-order model. Mechanism of adsorption process was also interpreted with the help of diffusion models and the results exhibited that external diffusion governed the overall sorption process. The Langmuir model yielded a good fit for the experimental data with high adsorption capacity (93.3 mg/g at 303 K). The evaluated thermodynamic parameters ΔG°, ΔH° and ΔS°, proposed that adsorption of OG was spontaneous, feasible, and exothermic under investigated conditions. Desorption experiments confirmed that the exhausted adsorbent can be successfully regenerated and can be effectively reused up to four successive cycles with almost the same sorption capacity resulting in reducing cost of treatment. The adsorption performance of alumina nanoparticles was also tested by using real wastewater and results indicated that nano alumina is proficient for the treatment of multi-solute system also. © 2016 The Authors
Keywords: Alumina nanoparticles; Isotherm; Kinetics; N2 adsorption-desorption; Regeneration; TGA/DTA